TRADITIONAL AGROECOSYSTEMS VS. ALTERNATIVE AGROECOSYSTEMS IN MAIZE IN CHIAPAS MEXICO - C. E. Aguilar-Jiménez; A. Tolón-Becerra; X. B. Lastra-Bravo (Journal of Animal and Plant Sciences, 2013)
The purpose of this study was to evaluate environmental variables in a traditional agroecosystem (TA - slash, fell and burn) and alternatives (AA - modifying the sowing density and rotating with Mucuna deeringiana Bort.), in Chiapas, Mexico. The variables were analyzed in two seasonal farming cycles, spring-summer (SS–burn) and autumn-winter (AW-no burn). Analysis of the environmental variables indicated better properties in TA, but there was no correlation with the years left fallow. The results were positive for AA, although it was found that TA had beneficial effects on certain variables as a result of being left fallow and adapting to the environment. A relative decrease was observed in the number of species, of individuals and of families as the fallow period was extended (R=67.7%). Modification of the sowing density affected maize yield positively (3.1 t/ha vs. 1.8 t/ha in TA). Models predicting yield well were found for both farming cycles (R=97.6% for SS and 97.3% for AW). It was observed that TA are attacked less by Diatraea liniolata Walker, because of the effect of fire on its reproduction. Both before burning and after harvest, soils were observed to be fertile with high content in nutrients, slightly acidic pH and good physical properties. Strong erosion was recorded from the beginning of the culture cycle, especially in TA (33.9 t/ha). The environmental sustainability of TA in the Selva Region was not affected over time by the reduction in fallow periods, but new agroecosystems must be found and implemented in the future.
Keywords: Slash; fell and burn agriculture; Traditional land use; Mucuna deeringiana Bort.; Maya Indians (indigenous people)